Comparative differences between T1a/b and T1e/m as substages in T1 urothelial carcinoma of the bladder - Turgay Turan (International Brazilian Journal of Urology)
ABSTRACT Objective To evaluate the prognostic value of the depth of lamina propria invasion in patients with T1 bladder cancer and to display comparative differences between the T1a/b and T1e/m substaging systems. Patients and Methods This study included 106 patients with primary stage T1 urothelial bladder tumours who underwent surgery between January 2009 and December 2014. Pathologic specimens were re-evaluated to confirm the diagnosis of T1 and substaging by the same pathologist using two systems: T1a and T1b, and T1m and T1e. Age, tumour size, multiplicity, associated carcinoma in situ, tumour grade, and T1 substaging system were investigated to detect the relation between disease progression and recurrence. Results The recurrence rate was 52% for T1a (n=42) vs. 76% for T1b (n=20) (p=0.028) and 55% for T1m (n=32) vs. 62% for T1e (n=30), respectively (p=0.446). There was no significant difference between the substaging groups for disease progression: T1a (n=12, 15%) vs. T1b (n=7, 27%), and T1m (n=8, 13.8%) vs. T1e (n=11, 23%) (p>0.05). In the multivariate analysis, tumour size >3 cm (p=0.008), multiplicity (p=0.049), and substaging T1b (p=0.043) were independent predictive factors for tumour recurrence. According to the Kaplan-Meier actuarial method, recurrence-free survival was significantly different in patients with pT1a tumours compared with those with pT1b tumours (p=0.033). Conclusions Substaging T1 provides a prediction of disease recurrence. Regarding recurrence, T1a/b substaging can provide better knowledge of disease behaviour because it is predicted as more superior than T1 m/e, and it can help in determining the requirement for early cystectomy.